Nucleic Acid and Non-Nucleic Acid-Based Reprogramming of Adult Limbal Progenitors to Pluripotency - Parameswaran, Sowmya (Public Library of Science, 2012)
Reprogramming somatic cells to a pluripotent state by nucleic acid based (NAB) approaches, involving the ectopic expression of transcription factors, has emerged as a standard method. We recently demonstrated that limbal progenitors that regenerate cornea are reprogrammable to pluripotency by a non-NAB approach through simple manipulation of microenvironment thus extending the possible therapeutic use of these readily accessible cells beyond the proven treatment of corneal diseases and injury. Therefore, to determine the validity and robustness of non-cell autonomous reprogramming of limbal progenitors for a wider clinical use, here, we have compared their reprogramming by non-NAB and NAB approaches. We observed that both approaches led to (1) the emergence of colonies displaying pluripotency markers, accompanied by a temporal reciprocal changes in limbal-specific and pluripotency gene expression, and (2) epigenetic alterations of Oct4 and Nanog, associated with the de-novo activation of their expression. While the efficiency of reprogramming and passaging of re-programmed cells were significantly better with the NAB approach, the non-NAB approach, in contrast, led to a regulated reprogramming of gene expression, and a significant decrease in the expression of Hormad1, a gene associated with immunogenic responses. The reprogramming efficiency by non-NAB approach was influenced by exosomes present in conditioned medium. Cells reprogrammed by both approaches were capable of differentiating along the three germ lineages and generating chimeras. The analysis suggests that both approaches are effective in reprogramming limbal progenitors but the non-NAB approach may be more suitable for potential clinical applications by averting the risk of insertional mutagenesis and immune responses associated with the NAB approach.